(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
Humans need to keep on the clean environment in order to refine suitable life for the next generators. Where, the different industries formed by human, cause the environmental pollution by landfill with wastes produced from it and cause the consumption of fresh raw materials. One of these industries, is gypsum plaster industry. Where, a large amount of gypsum plaster waste is produced from different fields that use the gypsum plaster. Therefore, it is necessary to work on reduction of these wastes by reusing or recycling them with the least costs and procedures. This study aims to review the ways used to reduce gypsum waste amount and to figure ant the best among them. It can be concluded that the best ways to reduce the gypsum waste amount are by recycling it with the least costs or reusing it without any additional procedures.